Tinjauan Kuat Geser Tanah Lempung Lunak Yang Distabilisasi Dengan Kolom Campuran Pasir Kapur Dengan Variasi Diameter - ENNI, MAR, Agus Susanto, S.T, M.T, Ir. Renaningsih, MT (2016)
According to research conducted by Merdhiyanto (2015) soil in the village Troketon Pedan Regency of Klaten included in the A-7-6 is soft clay with high plasticity. It resulted in structural damage to buldings located thereon such as the phenomenon of road cracks, subsidence and bumpy. One way to overcome these problems do soil stabilization by combining two materials of sand and lime. In this research, soil stabilization of the Troketon Village of Klaten Regency Pedan using a mixture of sand lime column with variation diameter. This test in terms of shear strength parameters of a value of cohesion (c) and angle friction (φ). The results show that stabilization with mixture of sand lime column value of cohesion (c) the most highest at 0,3534 kg/cm2, the value of angle friction at 7,030 and the value of shear strength at 0,554 kg/cm2 . In this study, the larger the diameter of the used value of cohesion (c) and the friction angle (φ) decrease, thus diameter of column a mixture of sand lime is the most effective at a diameter of 10 cm.